(n-6/3)=(n-2/9)

Simple and best practice solution for (n-6/3)=(n-2/9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (n-6/3)=(n-2/9) equation:



(n-6/3)=(n-2/9)
We move all terms to the left:
(n-6/3)-((n-2/9))=0
We add all the numbers together, and all the variables
(n-2)-((+n-2/9))=0
We get rid of parentheses
n-((+n-2/9))-2=0
We multiply all the terms by the denominator
n*9))-((+n-2-2*9))=0
We add all the numbers together, and all the variables
n*9))-((n-20))=0
We add all the numbers together, and all the variables
n*9))-((n=0
Wy multiply elements
9n^2=0
a = 9; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·9·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:
$n=\frac{-b}{2a}=\frac{0}{18}=0$

See similar equations:

| -6n+3=10n-7 | | 15+0.25x=20+.05x | | -6n+3=10n | | 2n-3n=9+2n | | 8.194=-3.4v+1.7v | | 1.50+1.5+p=11.50 | | 9(1.04)^x=9.36^x | | 24=-6r-6r | | 7y-15=5y+5 | | (1/5)n-1/3=8/3 | | x/4-7/2=-x/4 | | 24n=21 | | B+2b=26 | | |x^2+4x|=-12 | | 6(4x-3)-2(4x-10)=3(5x+3)-7 | | 1/5k-(k+1/2)=1/25(k+1) | | 3r-7=1-r | | 18=m=18 | | 7=1/6s+10 | | -7=m=8 | | 33=y/4+11 | | 1.4x+3.2=0 | | 180=45+k+2k | | 69+x=36 | | 7x-15=-4(-2x+2) | | 7x-15=-4(-2x+2 | | 1/8+x=6 | | 2(4x+2)=-4x-12(x-1) | | 4(x+3.8)=27.2 | | 24-x=3x+12 | | 15+4x=35 | | X=3t-4 |

Equations solver categories